REDEFINING THE POTENTIAL ROLE OF CHARISMATIC LANGUAGE TEACHERS IN CREATING SUPPORTIVE ACADEMIC ATMOSPHERE THROUGH STUDENTS’ MOTIVATIONAL AROUSAL - Adi Suryani (Jurnal Sosial Humaniora, 2025)
Charismatic language teachers have considerable potentials to nurture motivations in their students. They have personal magnetism which frequently they exhibit through their characters, communication, and how they develop relationship with their students. Charismatic teachers tend to be energetic, emphatic, warm, express confidence, love challenge, communicate vision, develop warm communication, put concern, trust, be inspiring and motivational. These characters allow them to be role model and inspire their motivation to their students. Their trusting behaviour also can lead to the creation of supportive classroom climate since supportive learning situation needs sense of autonomy. By having this sense of autonomy, students can voice their perspectives, beliefs and finally develop their autonomy self-regulation. By using their personal aura, charismatic language teachers can stimulate their students’ inner motivation.